2016
DOI: 10.21649/akemu.v22i3.1394
|View full text |Cite
|
Sign up to set email alerts
|

Professionalism in Medical Journalism and Role of HEC, PM&DC

Abstract: <p>The art of medical writing and science of scientific publishing has made tremendous progress during the last two decades. The revolution in information technology while on one hand has brought lot of ease and benefits, it has also created tremendous pressure and problems for the medial editors who are trying to come up to the expectations of authors who are very keen to see their manuscript published soon after submission.<sup>1,2</sup></p><p>      One can be a good physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…They can be helped to develop journal websites, setting up peer review system, use of manuscript processing, handling software’s like Open Journal System (OJS) or Editorial Manager etc., provide facilities for generating XML files for submission to PubMed Central or helping journals to get Indexed in important databases but so far it has fallen on deaf ears as those in authority were not prepared to work and dishing out money seems quite easy for them. 4 . 5 The contribution of regulatory bodies like PM&DC as well as HEC has so far been very disappointing but with the new interim set up in the PM&DC, involvement of a few professional medical editors in framing the Terms of Reference for the recognition and evaluation of medical journals, having some uniform policy by HEC and PM&DC, there are hopes that this communication gap between the regulatory bodies and the medical journal editors which has existed since long, will be bridged and the situation will improve in the coming few months.…”
Section: Role Of Regulatory Bodiesmentioning
confidence: 99%
“…They can be helped to develop journal websites, setting up peer review system, use of manuscript processing, handling software’s like Open Journal System (OJS) or Editorial Manager etc., provide facilities for generating XML files for submission to PubMed Central or helping journals to get Indexed in important databases but so far it has fallen on deaf ears as those in authority were not prepared to work and dishing out money seems quite easy for them. 4 . 5 The contribution of regulatory bodies like PM&DC as well as HEC has so far been very disappointing but with the new interim set up in the PM&DC, involvement of a few professional medical editors in framing the Terms of Reference for the recognition and evaluation of medical journals, having some uniform policy by HEC and PM&DC, there are hopes that this communication gap between the regulatory bodies and the medical journal editors which has existed since long, will be bridged and the situation will improve in the coming few months.…”
Section: Role Of Regulatory Bodiesmentioning
confidence: 99%
“…XML file developer). 1,[4][5][6] Free of cost publication of articles poses economic pressure on already struggling journals. The derecognition, or demotion followed by derecognition of the health science journal (HSJ) per its medical publication journey forever/indefinite period.…”
Section: Introductionmentioning
confidence: 99%
“…9 Published literature on roles of HEC e.g. digital library 10 or improvement in the quality of biomedical journals 6 can easily be accessed online. However, authors of the present study couldn't find a single paper on derecognition, demotion, or demotion followed by derecognition HEC-indexed Y and Z category HSJs.…”
Section: Introductionmentioning
confidence: 99%
“…It also offers financial grant to the journals depending on their category but this is not going to help improve standard of Pakistani biomedical journals. We have time and again suggested that instead of financial grant, let the HEC provide some services which the journals cannot afford themselves 3. For example, if it can acquire software for making XML files required by PubMed Central, a number of Pakistani biomedical journals will be able to move to PubMed Central thus improving their visibility to the international readers.…”
mentioning
confidence: 99%
“…We have time and again suggested that instead of financial grant, let the HEC provide some services which the journals cannot afford themselves. 3 For example, if it can acquire software for making XML files required by PubMed Central, a number of Pakistani biomedical journals will be able to move to PubMed Central thus improving their visibility to the international readers. Thus these journals will also automatically become visible on PubMed/Medline as well.…”
mentioning
confidence: 99%